2005
DOI: 10.1111/j.1540-6229.2005.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

The Other Side of Eight Mile: Suburban Population and Housing Supply

Abstract: This article establishes a linkage between decadal changes in suburban population and the supply of suburban dwelling units. It then estimates an econometric supply-and-demand model for 317 U.S. suburban areas for the 1970s, 1980s and 1990s using the State of the Cities database. Suburban supply is more elastic than central city supply, with suburban estimates between +1.26 and +1.42. However, separate estimates by geographic region lead to supply elasticities of +0.89 for the northeastern quadrant of the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…Land supply is an important determinant of housing supply elasticity (Goodman, 2005a(Goodman, , 2005bSaiz, 2010). When there is an adequate supply of land, developers are able to respond quickly to an increase in housing price by building more housing units.…”
Section: Housing Supply Elasticitymentioning
confidence: 99%
“…Land supply is an important determinant of housing supply elasticity (Goodman, 2005a(Goodman, , 2005bSaiz, 2010). When there is an adequate supply of land, developers are able to respond quickly to an increase in housing price by building more housing units.…”
Section: Housing Supply Elasticitymentioning
confidence: 99%
“…They also conclude that metropolitan area supply elasticities are lower in more regulated housing markets and in more densely populated cities. Goodman (2005b) estimates central city and suburban housing market supply elasticities over the 1970-2000 period using the US Department of Housing and Urban Development's (HUD's) State of the Cities Data System (SOCDS). He reports that suburban supply is more elastic than central city supply.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wubneh and Shen (2004) showed that this price-quality association leads to a negative effect on the property value of site-built homes from manufactured homes. In reference to literature on site built homes, price elasticity of demand ranges between À0.40 and À1.10, income elasticity of demand is spread from 0.89 to 1.46, and interest elasticity of demand from À.131 to À2.36 (Goodman and Kawai, 1984;Goodman, 1988Goodman, , 1990Goodman, , 2005Glennon, 1989;Harmon, 1988;Harrington, 1989). Estimates from studies on site built homes should provide an interesting comparison to those estimates obtained for the manufactured housing sector.…”
Section: Literature Reviewmentioning
confidence: 97%